Pleural empyema and exudative pleurisy: clinical experience, an integrated approach to evidence - Nevzghoda, Oleksandr; Shapovalov, Valentyn; Osyntseva, Alina; Shapovalova, Viktoriia; Shapovalov, Valerii (Annals of Mechnikov’s Institute, 2025)
Introduction. Antimicrobial resistance is one of the leading challenges for healthcare systems worldwide. The rational use of antibiotics in the pharmacotherapy of pleural empyema and exudative pleurisy requires the availability of substantiated clinical guidelines, state support for access to effective drugs and their adequate prescription in clinical practice. The aim of this study is to analyze clinical practice in the diagnosis and treatment of pleural empyema and exudative pleurisy, conduct a systematic network meta-analysis of antimicrobial drugs used in Ukraine, and determine their level of compliance with modern international and national guidelines. Materials and methods. A comparative analytical study of 32 international non-proprietary names of antibiotics mentioned in the DUODECIM guideline (Finland) was conducted. The sources of the analysis were national and international clinical guidelines, the State Register of Medicines of Ukraine, and the National List of Essential Medicines. The clinical practice of patients with pleural empyema and exudative pleurisy was studied (456 people). 412 primary and specialized medical care doctors from different regions of Ukraine were interviewed. Instrumental and general clinical examination methods, network meta-analysis, clinical-pharmacological, normative and graphic analysis were applied. Results. The clinical practice of patients with pleural empyema and exudative pleurisy was analyzed. The analysis of clinical guidelines (Recognition) showed that the largest number of mentions (4 out of 4 possible) were received by amoxicillin, ceftriaxone, azithromycin, levofloxacin. The assessment of availability (Availability) showed that most antibiotics are registered in Ukraine, but not all are included in the National List or the Equipment Table. The largest discrepancies were recorded for clarithromycin, fosfomycin, doxycycline. On an integral scale (0–8 points), all drugs were divided into three groups: priority (7–8 points), auxiliary (4–6), and underrepresented (0–3). A survey of doctors showed that amoxicillin, azithromycin, and ceftriaxone are most often prescribed, although some of the most used drugs (e.g. tetracycline, ampicillin) are not supported by clinical guidelines. In terms of ATS groups, the highest integral scores were received by macrolides (7.7 points), fluoroquinolones (7.3), and cephalosporins (6.9). A network meta-analysis allowed us to identify a core of 12 drugs that have a high level of support for all criteria. Visual graphs were constructed that demonstrate the structure of prescriptions, regulatory basis, and practical use. Discussion and recommendations. Based on an integrated assessment of clinical, clinical-pharmacological, and evidence-based practice, it is proposed to include in the National List or expand support for such drugs as clarithromycin, doxycycline, fosfomycin, and cefepime. The need to harmonize protocols, ensure the availability of drugs in procurement, update the Equipment Table, and intensify educational activities among doctors is emphasized. Conclusions. The integrated analysis allowed for a comprehensive assessment of the compliance of antimicrobial agents with the criteria of evidence, availability, and practical application. Priority antibiotics for the treatment of pleural empyema and exudative pleurisy were identified, which can be recommended for inclusion in clinical protocols, formularies, and national lists. The results obtained are important for the formation of a policy to combat antimicrobial resistance in Ukraine.